Effect of Transplanting Date on Growth and Yield of Hybrid and Inbreed Rice - Rabbi, Md Fazle; Hossain, Sumaia; Haque, Md Moinul; Islam, Mohammad Mahbub; Bithy, Parvin Akter (Research in Agriculture Livestock and Fisheries, 2025)
An experiment was conducted in the Experimental Field of Sher-e-Bangla Agricultural University, Dhaka to find out the effect of transplanting date on the growth and yield of hybrid and inbred rice. The experiment was carried out from November 2021 to April 2022. It comprised two factors viz, factor A: Varieties (Heera dhan2, BRRI dhan84, and BRRI dhan89) and factor B: Dates of transplanting (01 January, 15 January, 30 January, and 15 February). The experiment was laid out in a Randomized Complete Block Design (RCBD) with three replications. Data were collected on different aspects of growth, yield attributes, and yield. Regarding the interaction of variety and date of transplanting, the interaction of V1T1 (Heera dhan2 transplanted on 1st January) was the highest yielder (5.82 tha-1) among the other interactions, which was attributed to higher 1000-grain weight. The above result suggested and concluded that Heera dhan2 transplanting on 1st January provided the higher yield. Res. Agric. Livest. Fish. Vol. 12, No. 2, August 2025: 275-282